Networking Information Technologies as a Method Innovative Changes in Academic Libraries - Hovorukha, V. B.; Semenova, Larysa A.; Semenova, Liudmyla A. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Objective. The article examined at current global trends to require significant changes of the educational and library infrastructure. The analysis of these tendencies and of the current state of development of the educational and library sphere gave an opportunity to understand to the implementation of network technologies can affect to the activities of academic institutions. Methods. At the present stage, the popularity of distance technologies is increasing because they are best able to meet the new needs of modern users of library networks. The authors identified the factors of popularity and scope of networking technologies and investigated their influence on various aspects of the practical activity of university libraries. Results. Practical experience of the Scientific and Technical Library of DNURN named after academician V. Lazaryan demonstrates to the use of the modern networking technologies, which changed, improved and expanded the scope of services of the library institution. Conclusions. The research allows conclude to mastering library specialists of new knowledge and working skills to mobile information technologies. The introduction these technologies to practical activity promotes further development of the academic library and helps to improve forms of service for remote users to digital content